การปรับเปลี่ยนอุดมการณ์วารสารศาสตร์ของไทย - นวลวรรณ ดาระสวัสดิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The objective of this research, which employed qualitative approach, was to analyze the transformation of Thai journalistic ideology by studying the definition on journalistic ideology given by the prominent journalists and academicians from past to present. The study revealed that the journalists were both influenced by western ideologies and adapted each point of them at the same time. By this adaptation, they reserved the core content of these ideologies and adapted the detail of the subordinate idea to Thai social context in order to maintain the hegemonic intellectual group s power in Thai society. Freedom of the press and social responsibility were the main ideologies that were referred in their discourse from the past to present. The other ideologies such as accuracy, truth, fairness and professionalism were the subordinated ideologies that Thai journalists used as their framework. They also adapted the content of these ideologies to Thai social context during 3 different periods as below: 1. Absolute Monarchy Period: the journalists adapted the western ideologies by referring to the "Nationalism Discourse". The meaning of this discourse was interpreted by 2 groups ;the conservative courtiers and the progressiveness. The conservative courtiers interpreted that the freedom of the press was based on the truth and accuracy for the sake of the nation s benefit. On the contrary, the latter group believed that the freedom of the press could be expressed without any threat of power group. They could use it as a tool in demanding of the political revolution for the nation s prosperity and escaping from Imperialism. 2. Post-Democratic Revolution Period (1932): the journalists changed their reference from Nationalism to Self-Control Discourse. The meaning of this discourse was interpreted by 2 groups; the new-blood courtiers and the progressiveness. The first group interpreted that the freedom of the press should based on their limit of responsibility so that they would not be controlled of their freedom. The second group believed that their freedom of expression is unlimited and would not be controlled by any power group because it provided benefit to the country and Thai people as a whole. Moreover, it also created the linkage of the Nationalism ideology among their groups under the Noble Practice Discourse. 3. Contemporary period: the journalists changed their reference from the "Self-control Discourse" to "Credibility Discourse". The meaning of this discourse was interpreted by 2 groups; the journalistic academicians and prominent journalists. The academicians emphasized on the use of freedom under the frame of accuracy and truth while the journalists emphasized on their work based on the truth, non-prejudice. The freedom will be applied for the sake of Thai people. They also created the linkage among their groups by passing on their knowledge to their followers.